Low Density Wood-Based Particleboards Bonded with Foamable Sour Cassava Starch: Preliminary Studies - Sandra Monteiro (2016)
This work investigates the feasibility of producing low density particleboards using an adhesive system based on sour cassava starch, taking advantage of its adhesive and self-expansion properties. Relevant properties of the produced particleboards were evaluated according to European Standards including: density, internal bond, moisture content and thickness swelling. Low density particleboards were produced with densities between 207 kg/m(3) and 407 kg/m(3). The best performance corresponded to particleboard with a density of 318 kg/m(3), an internal bond strength of 0.67 N/mm(2), and a thickness swelling of 8.7%. These values meet the standard requirements of general purpose lightweight boards for use in dry conditions. Heat post-treatment (24 h at 80 degrees C) led to lower internal bond strength, due to retrogradation (recrystallization of amylose and amylopectin chains upon cooling) causing higher rigidity of the starch binder. However, it showed to have a significant effect on decreasing the thickness swelling.